Clinical epidemiological profile of vitiligo in children and adolescents - Flauberto de Sousa Marinho; Pablo Vitoriano Cirino; Nurimar C. Fernandes (Sociedade Brasileira de Dermatologia, 2013)
94 children and 25 adolescents, 42% male and 58% female, aged predominantly between six and ten years old (40%) were studied at the Martagão Gesteira Childcare and Pediatrics Institute (Rio de Janeiro Federal University) between 2005 and 2011. The prevalent clinical form of vitiligo was the generalized type (34%). Although the clinical response was similar between the treatment modalities, we decided for low and high power topical steroids in our routine. Halo nevi were found in seven (5.9%) cases. Thirty (25%) patients underwent specialized evaluation and 18 (60%) reported some relevant psychological situation.